Antibiotic use by poultry farmers in Kiambu County, Kenya: exploring practices and drivers of potential overuse - Kariuki, J.W.; Jacobs, J.; Ngogang, M.P.; Howland, Olivia (Springer, 2023)
Background Antibiotic resistance is a global concern threatening achievements in health care since the discovery of antibiotics. In Kenya, this topic remains understudied in a context of rising demand for livestock products, intensification and the concomitant increase in antibiotic use. Our study investigates drivers and practices of antibiotic use in poultry farming. The study was conducted in Kiambu County, Kenya.